Pengaruh Kinerja Keuangan Dan Kualitas Audit Terhadap Kualitas Laba - Bahri, Syaiful; Hartono, Arif (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
The research aims to analyze the influence of liquidity, profitability, leverage and audit quality on earnings quality in food and beverage companies listed on the Indonesian stock exchange for the 2020-2023 period. Important financial performance was re-examined due to inconsistencies in previous researchers' findings. Audit quality to prove the quality of the KAP which is classified as Big-4. The research sample was 13 companies using purposive sampling. Quantitative data types and secondary data sources with descriptive analysis, classical assumption test, multiple regression analysis, and t test. Liquidity, profitability and audit quality have a positive effect on earnings quality, while leverage has a negative effect on earnings quality. The high level of liquidity and profitability ensures that the profits presented reflect actual financial conditions. Asset financing is greater capital than debt so it shows good performance. Big-4 KAPs have lower manipulation than non-big-4 KAPs so they are able to produce quality earnings information. Big-4 KAPs maintain a good reputation in the market and auditors do not want disciplinary sanctions and have better audit resources.